2005
DOI: 10.1017/s0031182005008759
|View full text |Cite
|
Sign up to set email alerts
|

Gilthead seabream (Sparus aurataL.) innate defence against the parasiteEnteromyxum leei(Myxozoa)

Abstract: The humoral innate immune response of gilthead seabream (Sparus aurata L.) against the myxozoan Enteromyxum leei has been studied. At 10, 22, 38, 52 and 108 days of cohabitation fish were sampled to examine gut histology and to determine serum innate immune parameters and the mRNA expression of pro-inflammatory cytokines (IL-1beta and TNFalpha) in head-kidney. The parasite was successfully transmitted to 45% of the recipient fish and prevalence reached a maximum (62.5%) at the last sampling time (108 days). Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 56 publications
3
60
0
Order By: Relevance
“…Our results showed that this paramount leukocyte for the defence of GSB decreased in all examined tissues of R fish (PAR and NON-PAR, except in thymus), which may explain at least part of the limited protection of this species against the E. leei. In accordance, a decrease of the acidophilic granulocyte percentage (and consequent decrease in respiratory burst, phagocytic activity and leukocyte peroxidase) in the head kidney of E. leei-infected GSB was detected (Cuesta et al 2006c). On the other hand, the high serum peroxidase content found after E. leei exposure supports leukocyte mobilization into the circulatory system (Cuesta et al 2006b).…”
Section: Discussionmentioning
confidence: 68%
“…Our results showed that this paramount leukocyte for the defence of GSB decreased in all examined tissues of R fish (PAR and NON-PAR, except in thymus), which may explain at least part of the limited protection of this species against the E. leei. In accordance, a decrease of the acidophilic granulocyte percentage (and consequent decrease in respiratory burst, phagocytic activity and leukocyte peroxidase) in the head kidney of E. leei-infected GSB was detected (Cuesta et al 2006c). On the other hand, the high serum peroxidase content found after E. leei exposure supports leukocyte mobilization into the circulatory system (Cuesta et al 2006b).…”
Section: Discussionmentioning
confidence: 68%
“…The marked immunodepression in R-PAR fish is in accordance with the depletion of immune factors such as total serum peroxidases and lysozyme in fish exposed to E. leei , or the alternative complement pathway exhaustion observed in different species after chronic exposure to Enteromyxum spp. (Cuesta et al, 2006b;Sitjà-Bobadilla et al, 15 2006; Álvarez-Pellitero et al, 2008). In a subsequent study investigating the effects of gilthead sea bream nutritional status on E. leei disease progression, total serum peroxidases, lysozyme and nitric oxide were also significantly reduced in exposed fish fed either fish oil or a vegetable oil-based diet (Estensoro et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…In spite of the importance of this enteromyxosis, to date little is known about the mechanisms of infection, the parasite life-cycle, and some aspects of the host-parasite relationship, including the host immune response. Thus far, the humoral and cellular innate immune responses of gilthead sea bream (Cuesta et al, 2006a(Cuesta et al, , 2006bSitjà-Bobadilla et al, 3 2007; Sitjà- and sharpsnout sea bream (Golomazou et al, 2006;Muñoz et al, 2007;Álvarez-Pellitero et al, 2008) have been studied. Furthermore, the expression level of a small number of immunorelevant genes has been investigated (Cuesta et al, 2006b;Sitjà-Bobadilla et al, 2008) and clear differences have been observed in the expression profile of some of these genes between infected and non-infected fish.…”
Section: Introductionmentioning
confidence: 99%
“…It also downregulated growth hormone receptor-I and insulin-like growth factor-I in the head kidney. In a different study using the same infectious model, IL-1β expression in the head kidney was upregulated 10 days postinfection [14]. However, TNF-α expression was downregulated from 38 days postinfection onwards.…”
Section: Discussionmentioning
confidence: 88%
“…Antibody responses are not detected until weeks of chronic infection. Innate immune responses, like peroxidases, lysozyme, cytokines, or complement and adaptive immune responses, could be activated following myxosporean infection [13,14,15,16,17,18]. In this work, an accidental infection of Nile tilapia with myxosporean parasite was reported.…”
Section: Myxobolus (M) Pfeifferi M Musculi M Tauricus M Pseudomentioning
confidence: 83%